How Cardiac Embryology Translates into Clinical Arrhythmias - Mathilde R. Rivaud; Michiel Blok; Monique R. M. Jongbloed; Bastiaan J. Boukens (Journal of Cardiovascular Development and Disease, 2021)
The electrophysiological signatures of the myocardium in cardiac structures, such as the atrioventricular node, pulmonary veins or the right ventricular outflow tract, are established during development by the spatial and temporal expression of transcription factors that guide expression of specific ion channels. Genome-wide association studies have shown that small variations in genetic regions are key to the expression of these transcription factors and thereby modulate the electrical function of the heart. Moreover, mutations in these factors are found in arrhythmogenic pathologies such as congenital atrioventricular block, as well as in specific forms of atrial fibrillation and ventricular tachycardia. In this review, we discuss the developmental origin of distinct electrophysiological structures in the heart and their involvement in cardiac arrhythmias.